Peran Kompensasi dalam Meningkatkan Kinerja Karyawan: Kajian Literatur - Cininta Nareswari Pratiwi; Agung Zulfikri (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
This study was conducted to examine the effect of compensation on employee performance through a literature review approach. The background of this research is based on the importance of compensation as a factor that contributes to improving employee work outcomes. Compensation is not only considered as remuneration for work performed, but also as an element that can encourage motivation and productivity. The study applied a descriptive method using a literature review approach. The data used were secondary data obtained from 20 national scientific journals published since 2020, discussing compensation and employee performance. Data collection was carried out through library research by selecting, classifying, and reviewing relevant literature sources. Furthermore, the data were analyzed descriptively by interpreting findings from previous studies. The results indicate that 19 out of 20 journals reported a positive and significant relationship between compensation and employee performance. Therefore, it can be concluded that compensation plays an essential role in enhancing employee performance, making an effective compensation system a crucial aspect of human resource management.